Principles of Safety Pharmacology - Michael K. Pugsley; Simon Authier; Michael J. Curtis (2008)
Safety Pharmacology is a rapidly developing discipline that uses the basic principles of pharmacology in a regulatory-driven process to generate data to inform risk/benefit assessment. The aim of Safety Pharmacology is to characterize the pharmacodynamic/pharmacokinetic (PK/PD) relationship of a drug's adverse effects using continuously evolving methodology. Unlike toxicology, Safety Pharmacology includes within its remit a regulatory requirement to predict the risk of rare lethal events. This gives Safety Pharmacology its unique character. The key issues for Safety Pharmacology are detection of an adverse effect liability, projection of the data into safety margin calculation and finally clinical safety monitoring. This article sets out to explain the drivers for Safety Pharmacology so that the wider pharmacology community is better placed to understand the discipline. It concludes with a summary of principles that may help inform future resolution of unmet needs (especially establishing model validation for accurate risk assessment). Subsequent articles in this issue of the journal address specific aspects of Safety Pharmacology to explore the issues of model choice, the burden of proof and to highlight areas of intensive activity (such as testing for drug-induced rare event liability, and the challenge of testing the safety of so-called biologics (antibodies, gene therapy and so on.).